A quinoline bipyrimidine compound and its application in organic electroluminescent element
By using quinoline bipyrimidine compounds as electron transport materials, the problems of low carrier mobility and poor thermal stability are solved, the luminescence efficiency and life of organic electroluminescent devices are improved, and the working voltage is reduced, thus achieving the Better thermal stability and film forming properties.
Patent Information
- Application Number
- CN202111095582.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-17
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-09-17
AI Technical Summary
The carrier mobility of existing electron transport materials is low and the thermal stability is poor, resulting in the rapid roll-off of the luminous efficiency of organic electroluminescent elements and poor device life. The hole mobility of hole transport materials is much greater than that of electrons. The electron mobility of the transport material leads to a degradation of device performance.
Quinoline bipyrimidine compounds are used as electron transport material to improve electron transport efficiency and thermal stability through specific aryl structures and connection methods, reduce working voltage, and enhance the luminous efficiency and life of the device.
有效降低了有机电致发光器件的工作电压,提高了发光效率和寿命,且喹啉联嘧啶化合物的玻璃化转变温度高,成膜性好,热稳定性优异,避免了光散射和结晶问题。
Smart Images

Figure CN115819399B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electron transport materials, and in particular to a quinoline bipyrimidine compound and application thereof in an organic electroluminescent element. Background Art
[0002] Organic light emitting diodes (OLED) have the advantages of being light, thin, self-luminous, low power consumption, no backlight, wide viewing angle, fast response and flexibility. They have gradually replaced liquid crystal display panels to become a new generation of flat panel displays, and they also have great potential in flexible displays. The carrier mobility of traditional electron transport materials is one thousandth of that of hole transport materials, and their thermal stability is poor, which often leads to problems such as rapid roll-off of luminous efficiency or poor device life. According to relevant literature, the charge consumption ratio of electron transport materials is as high as 35.9%, second only to the consumption of the light-emitting layer (39.8%). Therefore, the development of electron transport materials with high carrier mobility and good thermal stability is one of the current focuses of OLED material development.
[0003] Good electron transport materials usually need to meet the following characteristics: (1) LUMO energy level matching that of the light-emitting layer to facilitate electron transfer; (2) HOMO energy level lower than that of the light-emitting layer to facilitate confinement of excitons in the light-emitting layer; (3) triplet energy level T1 that is high enough when matched with phosphorescent materials to avoid exciton quenching; (4) amorphous phase to avoid light scattering; (5) good thermal stability and high glass transition temperature.
[0004] At present, the commonly used electron transport materials mainly include metal complexes, nitrogen-containing heterocyclic compounds, perfluorinated compounds, organosilicon compounds, organoboron compounds, etc. Among them, nitrogen-containing heterocyclic compounds are the most studied structures. Using their doped metal complexes as the electron transport layer of red organic phosphorescent elements can improve the electron transport efficiency on the one hand, and on the other hand, the life span is also significantly improved. At present, the hole mobility of the hole transport material in the existing OLED device is generally much greater than the electron mobility of the electron transport material. This imbalance in the carrier transport rate will lead to a significant decrease in device performance. Therefore, only with good electron mobility can electrons be effectively transported to the recombination area away from the cathode. In addition, the electron transport material must have good film-forming properties, otherwise it cannot form a uniform thin film during evaporation, and crystallization is easy to occur, which seriously affects the efficiency and life of the device. Therefore, the performance of the electron transport material needs to be further optimized to achieve low voltage, high efficiency and long life of the device. Summary of the invention
[0005] The main purpose of the present invention is to provide a quinoline bipyrimidine compound, which can be used as an electron transport material in an organic electroluminescent device. The use of the compound of the present invention can effectively reduce the operating voltage of the organic electroluminescent device and improve the luminous efficiency and life of the device.
[0006] In order to achieve the above object, according to one aspect of the present invention, a quinoline bipyrimidine compound is provided, and the quinoline bipyrimidine compound has a structure shown in the following general formula A:
[0007]
[0008] Wherein, Ar1 and Ar2 are the same or different and are independently selected from C6 to C 30 aryl or heteroaryl, L is selected from a direct bond or a C6~C 18 of unsubstituted aryl.
[0009] Furthermore, the above Ar1 and Ar2 are the same and are selected from C 10 ~C 18 The aryl or heteroaryl group.
[0010] Furthermore, the above Ar1 and Ar2 are different and are selected from C6 to C 30 The aryl or heteroaryl group.
[0011] Furthermore, the above Ar1 and Ar2 are selected from biphenyl, naphthyl, anthracenyl, phenanthryl, dimethylfluorenyl, dibenzofuranyl or dibenzothiophenyl.
[0012] Furthermore, the above Ar1 and Ar2 are selected from phenyl, biphenyl, naphthyl, anthracenyl, phenanthryl, dimethylfluorenyl, dibenzofuranyl or dibenzothiophenyl.
[0013] Furthermore, the above-mentioned quinoline bipyrimidine compound is selected from any one of the following:
[0014]
[0015]
[0016]
[0017]
[0018]
[0019] BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0021] Figure 1 A schematic structural diagram of an organic electroluminescent device provided by an embodiment of the present invention is shown.
[0022] The above drawings include the following reference numerals:
[0023] 1. Substrate layer; 2. Hole injection layer; 3. Hole transport layer; 4. Light-emitting layer; 5. Electron transport layer; 6. Cathode layer. DETAILED DESCRIPTION
[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0025] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.
[0026] First, the synthesis method of the quinolinebipyrimidine compound of the present application is illustrated below.
[0027] Synthesis Example
[0028] 1. Synthesis of intermediates
[0029] 1.1 Synthesis of intermediate M1
[0030]
[0031] 2,4-Dichloroquinoline (9.9g, 50mmol), 2-naphthaleneboronic acid (8.77g, 51mmol), 150mL toluene, potassium carbonate (13.82g, 100mmol), 50mL water, 50mL ethanol were added to a 500mL round-bottom flask, stirred and heated to 50°C under nitrogen protection, 0.58g catalyst Pd(PPh3)4 was added, and the temperature was continued to rise to reflux reaction for 4h before stopping the reaction, cooling and separating, the organic phase was washed twice with 50mL water, heated toluene and passed through a short silica gel column for decolorization, and then the toluene was evaporated to about 50mL, heated to 80°C and dissolved, 200mL ethanol was added, stirred and cooled to precipitate solid, filtered and dried, and 12g white solid compound M1 was obtained with a yield of 83%. Intermediate M1 was further recrystallized twice by the same method, with a purity of 99.2%.
[0032] 1.2 Synthesis of intermediate M2
[0033]
[0034] Compound M1 (15 g, 51.7 mmol), bis-pinacol borate (14.4 g, 56.9 mmol), 200 mL toluene, and 6.6 g potassium acetate were added to a 500 mL round-bottom flask, stirred and heated to 50°C under nitrogen protection, 0.29 g catalyst Pd(dba)2 and 0.48 g 2-di-tert-butylphosphine-2',4',6'-triisopropylbiphenyl were added, and the temperature was continued to rise to reflux for 6 hours before stopping the reaction. The organic phase was decolorized by passing through a short silica gel column while hot, and then the toluene was evaporated. After cooling, 20 mL of dichloromethane was added and heated to 40°C to dissolve completely, and then 150 mL of n-hexane was added, stirred and cooled to precipitate solids, filtered and dried to obtain 15 g of white solid compound M2 with a yield of 76.1%. The purity was 99.3%.
[0035] 1.3 Synthesis of intermediate M3
[0036]
[0037] 2,4-Dichloroquinoline (9.9g, 50mmol), 9-phenanthrene boronic acid (11.3g, 51mmol), 150mL toluene, potassium carbonate (13.82g, 100mmol), 50mL water, 50mL ethanol were added to a 500mL round-bottom flask, stirred and heated to 50°C under nitrogen protection, 0.58g catalyst Pd(PPh3)4 was added, and the temperature was continued to rise to reflux reaction for 4h before stopping the reaction, cooling and separating, the organic phase was washed twice with 50mL water, heated toluene and passed through a short silica gel column for decolorization, and then the toluene was evaporated to about 100mL, heated to 80°C and dissolved, 100mL ethanol was added, stirred and cooled to precipitate solids, filtered and dried, and 15.6g white solid compound M3 was obtained with a yield of 92%. Intermediate M3 was further recrystallized twice by the same method, with a purity of 99.2%.
[0038] 1.4 Synthesis of intermediate M4
[0039]
[0040] Compound M3 (10 g, 29.4 mmol), bis-pinacol borate (8.96 g, 35.3 mmol), 100 mL toluene and 4.42 g potassium acetate were added to a 250 mL round-bottom flask, stirred and heated to 50°C under nitrogen protection, 0.14 g catalyst Pd2(dba)3 and 0.14 g 2-di-tert-butylphosphino-2',4',6'-triisopropylbiphenyl were added, and the temperature was continued to rise to reflux for 8 hours before stopping the reaction. The organic phase was decolorized by passing through a short silica gel column while hot, and then the toluene was evaporated to about 30 mL and heated to 80°C for complete dissolution, and then 100 mL of n-hexane was added, stirred and cooled to precipitate solid, filtered and dried to obtain 9.7 g of white solid compound M4 with a yield of 75%. The purity was 98.7%.
[0041] 1.5 Synthesis of intermediate M5
[0042]
[0043] 2,4-Dichloroquinoline (9.9g, 50mmol), dibenzothiophene-2-boric acid (11.6g, 51mmol), 150mL toluene, potassium carbonate (13.82g, 100mmol), 50mL water, 50mL ethanol were added to a 500mL round-bottom flask, stirred and heated to 50°C under nitrogen protection, 0.58g catalyst Pd(PPh3)4 was added, and the temperature was continued to rise to reflux reaction for 4h before stopping the reaction, cooling and separating, the organic phase was washed twice with 50mL water, heated toluene and passed through a short silica gel column for decolorization, and then the toluene was evaporated to about 100mL, heated to 80°C and dissolved, 100mL ethanol was added, stirred and cooled to precipitate solids, filtered and dried, and 15.2g white solid compound M5 was obtained with a yield of 86%. Intermediate M5 was further recrystallized twice by the same method, with a purity of 99.2%.
[0044] 1.6 Synthesis of intermediate M6
[0045]
[0046] The intermediate M5 (12 g, 34.7 mmol), bis-pinacol borate (9 g, 38.2 mmol), 150 mL toluene and 6.9 g potassium acetate were added to a 250 mL round-bottom flask, stirred and heated to 50°C under nitrogen protection, 0.16 g catalyst Pd2(dba)3 and 0.16 g 2-di-tert-butylphosphino-2',4',6'-triisopropylbiphenyl were added, and the temperature was continued to rise to reflux for 16 hours before stopping the reaction. The organic phase was decolorized by passing through a short silica gel column while hot, and then the toluene was evaporated to 50 mL and heated to 80°C for complete dissolution, and then 100 mL of n-hexane was added, stirred and cooled to precipitate solids, filtered and dried to obtain 10.4 g of white solid compound M6 with a yield of 68% and a purity of 98.4%.
[0047] 1.7 Synthesis of intermediate M7
[0048]
[0049] 2,4-Dichloroquinoline (9.9g, 50mmol), 4-biphenylboronic acid (10.1g, 51mmol), 150mL toluene, potassium carbonate (13.82g, 100mmol), 50mL water, 50mL ethanol were added to a 500mL round-bottom flask, stirred and heated to 50°C under nitrogen protection, 0.58g catalyst Pd(PPh3)4 was added, and the temperature was continued to rise to reflux reaction for 4h before stopping the reaction, cooling and separating, the organic phase was washed with 50mL water twice, heated toluene and passed through a short silica gel column for decolorization, and then the toluene was evaporated to about 50mL, heated to 80°C and dissolved, 200mL ethanol was added, stirred and cooled to precipitate solids, filtered and dried, and 14.2g white solid compound M7 was obtained with a yield of 90%. Intermediate M7 was further recrystallized twice by the same method, with a purity of 99.1%.
[0050] 1.8 Synthesis of intermediate M8
[0051]
[0052] The intermediate M7 (12 g, 38 mmol), bis-pinacol borate (10.6 g, 41.8 mmol), 150 mL toluene and 5.6 g potassium acetate were added to a 250 mL round-bottom flask, stirred and heated to 50°C under nitrogen protection, 0.17 g catalyst Pd2(dba)3 and 0.17 g 2-di-tert-butylphosphino-2',4',6'-triisopropylbiphenyl were added, and the temperature was continued to rise to reflux for 8 hours before stopping the reaction. The organic phase was decolorized by passing through a short silica gel column while hot, and then toluene was evaporated to 80 mL and heated to 80°C for complete dissolution, and then 100 mL of n-hexane was added, stirred and cooled to precipitate solids, filtered and dried to obtain 10.4 g of white solid compound M8 with a yield of 67% and a purity of 98.5%.
[0053] 1.9 Synthesis of intermediate M9
[0054]
[0055] 2,4,6-trichloropyrimidine (18.3 g, 100 mmol), 2-naphthaleneboronic acid (34.6 g, 201 mmol), 500 mL toluene, potassium carbonate (55.3 g, 400 mmol), 200 mL water, and 200 mL ethanol were added to a 2000 mL round-bottom flask, stirred and heated to 50 ° C under nitrogen protection, 2.1 g catalyst PdCl2 (PPh3) 2 was added, and the temperature was continued to rise to reflux reaction for 8 hours before stopping the reaction, cooling and separating, the organic phase was spin-dried, 500 mL toluene was added and heated through a short silica gel column for decolorization, and then the toluene was evaporated to 200 mL and heated to 110 ° C for complete dissolution, stirred and cooled to precipitate solids, filtered and dried to obtain 27.1 g white solid compound M9, with a yield of 74%. Intermediate M9 was further recrystallized once by the same method, with a purity of 99.5%.
[0056] 1.10 Synthesis of intermediate M10
[0057]
[0058] 2,4,6-trichloropyrimidine (18.24 g, 100 mmol), 4-biphenylboronic acid (41.6 g, 210 mmol), 500 mL toluene, sodium carbonate (31.8 g, 300 mmol), 150 mL water, and 100 mL ethanol were added to a 1000 mL round-bottom flask, stirred and heated to 50 ° C under nitrogen protection, 3.4 g catalyst Pd (PPh3) 4 was added, and the reaction was stopped after continuing to heat to reflux reaction for 8 hours, and the temperature was cooled and filtered to separate the liquid. The organic phase was washed twice with 100 mL water, filtered and combined, 500 mL toluene was added and heated through a short silica gel column for decolorization, and then the toluene was evaporated to 100 mL, stirred and cooled to precipitate the solid, filtered and dried, and 28.5 g of white solid compound M10 was obtained with a yield of 78%. Intermediate M10 was further recrystallized twice by the same method, and the purity was 99.6%.
[0059] 2. Synthesis of target compounds
[0060] 2.1 Synthesis of Compound A4
[0061]
[0062] Intermediate M2 (10 g, 26.2 mmol), intermediate M7 (25 mmol), 100 mL tetrahydrofuran, potassium carbonate (6.91 g, 40 mmol), and 30 mL water were added to a 250 mL round-bottom flask, stirred and heated to 40° C. under nitrogen protection, 56 mg catalyst Pd (OAc) 2, 0.24 g 2-di-tert-butylphosphine-2', 4', 6'-triisopropylbiphenyl were added, and the reaction was stopped after continuing to heat to reflux reaction for 6 hours, and the liquid was filtered and separated after cooling, the organic phase was spin-dried and combined with the filtered solid, 600 mL toluene was added and heated through a short silica gel column for decolorization, and then toluene was evaporated until solid precipitation, stirred and cooled to room temperature, filtered and dried to obtain white solid compound A4. Compound A4 was further recrystallized twice by the same method, with a purity of more than 99.5%, and further purified twice by vacuum sublimation, with a purity of 99.92%.
[0063] 2.2 Synthesis of other target compounds
[0064] Different intermediates were selected, and other target compounds were synthesized by referring to the synthesis of compound A4, and finally purified by vacuum sublimation, as shown in Table 1.
[0065] Table 1
[0066]
[0067]
[0068]
[0069] The characterization results of the compounds are as follows:
[0070] Compound A4: 1H NMR (400 MHz, CDCl3). δ8.85 (t, J = 3.0 Hz, 1H), 8.73 (s, 1H), 8.46 (t, J = 2.9 Hz, 2H), 8.42-8.33 (m, 2H), 8.15-7.93 (m, 12H), 7.88 (dd, J = 14.8, 3.1 Hz, 1H), 7.74 (td, J = 14.9, 3.1 Hz, 1H), 7.68-7.51 (m, 7H).
[0071] Compound A27: 1H NMR (400 MHz, CDCl3). δ8.87 (t, J = 3.0 Hz, 1H), 8.75 (s, 1H), 8.41-8.25 (m, 6H), 8.14-7.96 (m, 4H), 7.92-7.80 (m, 5H), 7.80-7.68 (m, 5H), 7.64-7.29 (m, 9H).
[0072] Compound A53: 1H NMR (400 MHz, CDCl3). δ9.08 (dd, J = 14.6, 3.4 Hz, 1H), 8.84 (dd, J = 14.2, 3.7 Hz, 1H), 8.73 (s, 1H), 8.42 (d, J = 3.1 Hz, 1H), 8.21-8.06 (m, 3H), 7.92 (dddd, J = 14.9, 11.6, 7.0, 2.5 Hz, 6H), 7.79-7.37 (m, 12H).
[0073] Compound A54: 1H NMR (400 MHz, CDCl3). δ8.96 (dd, J = 14.6, 3.4 Hz, 1H), 8.72 (dd, J = 14.2, 3.7 Hz, 1H), 8.61 (s, 1H), 8.37–8.31 (m, 3H), 8.11 (s, 1H), 8.09–7.72 (m, 12H), 7.67–7.38 (m, 10H).
[0074] Compound A56: 1H NMR (400 MHz, CDCl3). δ8.86 (dd, J = 14.6, 3.4 Hz, 1H), 8.62 (dd, J = 14.2, 3.7 Hz, 1H), 8.51 (s, 1H), 8.21 (d, J = 3.1 Hz, 1H), 8.13–8.03 (m, 4H), 8.02–7.84 (m, 3H), 7.73–7.58 (m, 6H), 7.58–7.07 (m, 16H).
[0075] Compound A65: 1H NMR (400 MHz, CDCl3). δ8.75–8.64 (m, 3H), 8.46 (t, J = 2.9 Hz, 2H), 8.34 (s, 1H), 8.14–7.94 (m, 9H), 7.86 (dq, J = 6.0, 3.3 Hz, 3H), 7.79–7.69 (m, 3H), 7.67–7.38 (m, 8H).
[0076] Compound A95: 1H NMR (400 MHz, CDCl3). δ8.73 (s, 1H), 8.62 (d, J = 2.9 Hz, 1H), 8.31 (s, 1H), 8.10 (dd, J = 15.0, 3.1 Hz, 1H), 8.06–7.84 (m, 7H), 7.73 (ddd, J = 19.8, 15.6, 9.1 Hz, 2H), 7.61–7.25 (m, 10H).
[0077] 3. Characterization of Thermodynamic Properties
[0078] The glass transition temperature Tg was measured by differential scanning calorimetry (DSC, DSC25 differential scanning calorimeter from TA Company, USA) with a heating rate of 10°C / min; the decomposition temperature Td was the temperature at which the weight loss was 5% in a nitrogen atmosphere, and was measured on a TGA55 thermogravimetric analyzer from TA Company, USA, with a nitrogen flow rate of 20 mL / min. The specific data are shown in Table 2 below.
[0079] Table 2
[0080] Compound Tg(℃) Td(℃) A4 87 432 A27 109 458 A53 108 400 A54 139 465 A56 124 469 A65 100 456 A95 125 440
[0081] From the data in the table, it can be seen that the glass transition temperature of the quinoline bipyrimidine compound represented by the general formula A used in the present invention is above 85°C, it is not easy to crystallize, and has good film-forming properties. The thermal decomposition temperature is above 400°C, it is not easy to decompose, and has excellent thermal stability.
[0082] 4. Preparation of organic electroluminescent elements
[0083] The above organic compounds of the present invention are particularly suitable for the electron transport layer in OLED devices. Figure 1 The device structure of the present invention is described in detail through specific embodiments to illustrate the application effect of the organic compound of the present invention as an electron transport layer in the OLED device.
[0084] The structural formula of the organic materials used is as follows:
[0085]
[0086] The organic electroluminescent element using the quinoline bipyrimidine compound of the present invention as an electron transport layer may include a glass and transparent conductive layer (ITO) substrate layer 1, a hole injection layer 2, a hole transport layer 3, a light emitting layer 4, an electron transport layer 5, and a cathode layer 6.
[0087] Device Example 1
[0088] Reference Figure 1 The structure shown in the figure is used to manufacture the OLED device using a Sunic sp1710 evaporation machine. The specific steps are as follows: a glass substrate (Corning glass 40mm×40mm×0.7mm) coated with ITO (indium tin oxide) with a thickness of 135nm is ultrasonically cleaned with isopropyl alcohol and pure water for 5 minutes respectively, and then cleaned with ultraviolet ozone, and then the glass substrate is transferred to a vacuum deposition chamber; a hole transport material HT1 doped with 4% HD is vacuum-deposited with a thickness of 20nm (about 10 -7Torr) is thermally deposited on a transparent ITO electrode to form a hole injection layer; HT1 with a thickness of 150nm and HT2 with a thickness of 5nm are then vacuum deposited on the hole injection layer as a hole transport layer; BH doped with 2% BD is vacuum deposited with a thickness of 25nm on the hole transport layer as a light-emitting layer; then compound A4 doped with 50% LiQ (8-hydroxyquinoline lithium) is vacuum deposited to form an electron transport layer with a thickness of 30nm; finally, 2nm thick metal ytterbium (Yb, electron injection layer) and 150nm of magnesium-silver alloy with a doping ratio of 10:1 are sequentially deposited to form a cathode; finally, the device is transferred from the deposition chamber to a glove box and then encapsulated with a UV-curable epoxy resin and a glass cover containing a desiccant.
[0089] In the above manufacturing steps, the deposition rates of the organic material, metal ytterbium, and metal Mg were maintained at 0.1 nm / s, 0.05 nm / s, and 0.2 nm / s, respectively.
[0090] The device structure is represented as: ITO (135nm) / HT1: 4% HD (20nm) / HT1 (150nm) / HT2 (5nm) / BH: 2% BD (25nm) / Compound A4: LiQ (5:5, 30nm) Yb (2nm) / Mg: Ag (10:1, 150nm)
[0091] Device Example 2
[0092] The experiment was performed in the same manner as in Device Example 1, except that as the electron transport layer, Compound A27 was used instead of Compound A4 in Device Example 1.
[0093] The device structure is represented as: ITO (135nm) / HT1: 4% HD (20nm) / HT1 (120nm) / HT2 (10nm) / BH: 2% BD (25nm) / Compound A27: LiQ (5:5, 30nm) Yb (2nm) / Mg: Ag (10:1, 150nm)
[0094] Device Example 3
[0095] The experiment was performed in the same manner as in Device Example 1, except that as the electron transport layer, Compound A53 was used instead of Compound A4 in Device Example 1.
[0096] The device structure is represented as: ITO (135nm) / HT1: 4% HD (20nm) / HT1 (120nm) / HT2 (10nm) / BH: 2% BD (25nm) / Compound A53: LiQ (5:5, 30nm) Yb (2nm) / Mg: Ag (10:1, 150nm)
[0097] Device Example 4
[0098] The experiment was performed in the same manner as in Device Example 1, except that as the electron transport layer, Compound A54 was used instead of Compound A4 in Device Example 1.
[0099] The device structure is represented as: ITO (135nm) / HT1: 4% HD (20nm) / HT1 (120nm) / HT2 (10nm) / BH: 2% BD (25nm) / Compound A54: LiQ (5:5, 30nm) Yb (2nm) / Mg: Ag (10:1, 150nm)
[0100] Device Example 5
[0101] The experiment was performed in the same manner as in Device Example 1, except that as the electron transport layer, Compound A56 was used instead of Compound A4 in Device Example 1.
[0102] The device structure is represented as: ITO (135nm) / HT1: 4% HD (20nm) / HT1 (120nm) / HT2 (10nm) / BH: 2% BD (25nm) / Compound A56: LiQ (5:5, 30nm) Yb (2nm) / Mg: Ag (10:1, 150nm)
[0103] Device Example 6
[0104] The experiment was performed in the same manner as in Device Example 1, except that as the electron transport layer, Compound A65 was used instead of Compound A4 in Device Example 1.
[0105] The device structure is represented as: ITO (135nm) / HT1: 4% HD (20nm) / HT1 (120nm) / HT2 (10nm) / BH: 2% BD (25nm) / Compound A65: LiQ (5:5, 30nm) Yb (2nm) / Mg: Ag (10:1, 150nm)
[0106] Device Example 7
[0107] The experiment was performed in the same manner as in Device Example 1, except that as the electron transport layer, Compound A95 was used instead of Compound A4 in Device Example 1.
[0108] The device structure is represented as: ITO (135nm) / HT1: 4% HD (20nm) / HT1 (120nm) / HT2 (10nm) / BH: 2% BD (25nm) / Compound A95: LiQ (5:5, 30nm) Yb (2nm) / Mg: Ag (10:1, 150nm)
[0109] Device Comparative Example 1
[0110] The experiment was performed in the same manner as in Device Example 1, except that as the electron transport layer, Compound M was used instead of Compound A4 in Device Example 1.
[0111] The device structure is represented as: ITO (135nm) / HT1: 4% HD (20nm) / HT1 (120nm) / HT2 (10nm) / BH: 2% BD (25nm) / Compound M: LiQ (5:5, 30nm) Yb (2nm) / Mg: Ag (10:1, 150nm)
[0112] The device brightness, luminous efficiency, and EQE (external quantum efficiency) were tested by Suzhou Fushida FS-100GA4, and the device life LT98 (the time taken for the initial brightness to decay to 3920 nits from 4000 nits, normalized with the device control ratio as a reference) was tested by Fushida FS-MP96. All measurements were completed in room temperature atmosphere. 2 The specific performance data of the operating voltage (V), current efficiency (CE), power efficiency (PE), external quantum efficiency (EQE) and color coordinates (CIEx, CIEy) under current density are shown in Table 3.
[0113] Table 3
[0114]
[0115] Compared with device comparison example 1, the device using the quinoline bipyrimidine compound of the present invention as an electron transport material has a significantly reduced voltage, a significantly improved efficiency, and a significantly improved lifespan. This is because pyrimidine has a stronger electronegativity than pyridine, and pyrimidine is connected to the quinoline molecule at position 2, which can improve the molecular planarity and better electron transfer ability.
[0116] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A quinoline bipyrimidine compound, characterized in that: The quinoline bipyrimidine compound has a structure shown in the following general formula A: wherein Ar1 and Ar2 are the same, and are selected from biphenyl, naphthyl, anthracenyl, phenanthryl, dimethylfluorenyl, dibenzofuranyl or dibenzothienyl; or Ar1 and Ar2 are different and are each independently selected from phenyl, biphenyl, naphthyl, anthracenyl, phenanthryl, dimethylfluorenyl, dibenzofuranyl or dibenzothienyl, and L is selected from a direct bond or an unsubstituted phenylene group.
2. The quinoline bipyrimidine compound according to claim 1, characterized in that The quinoline bipyrimidine compound is selected from any one of the following:
3. The quinoline bipyrimidine compound according to claim 1 or 2, characterized in that The quinolinebipyrimidine compound can be used as an electron transport material in an organic electroluminescent element.
Citation Information
Patent Citations
A plurality of host materials and organic electroluminescent device comprising the same
CN108780853A
Heterocyclic compound and organic light emitting element using same
CN110944991A
